2021
DOI: 10.1038/s41388-021-01950-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in obesity-associated hepatocellular carcinoma: sources, signaling and therapeutic challenges

Abstract: Obesity affects more than 650 million individuals worldwide and is a well-established risk factor for the development of hepatocellular carcinoma (HCC). Oxidative stress can be considered as a bona fide tumor promoter, contributing to the initiation and progression of liver cancer. Indeed, one of the key events involved in HCC progression is excessive levels of reactive oxygen species (ROS) resulting from the fatty acid influx and chronic inflammation. This review provides insights into the different intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 122 publications
0
31
0
Order By: Relevance
“…Abnormal antioxidative response via aberrant Kelch-like ECH-associated protein 1 (Keap1)- nuclear factor erythroid 2-related factor 2 (NRF2) signaling is a common event in the progression of HCC [ 96 ]. TRIM25 promotes ubiquitin degradation of Keap1, therefore over-activating NRF2 to alleviate oxidative stress and reduce apoptosis in HCC [ 97 ].…”
Section: Effects Of Trim Proteins On Hallmarks Of Carcinogenesismentioning
confidence: 99%
“…Abnormal antioxidative response via aberrant Kelch-like ECH-associated protein 1 (Keap1)- nuclear factor erythroid 2-related factor 2 (NRF2) signaling is a common event in the progression of HCC [ 96 ]. TRIM25 promotes ubiquitin degradation of Keap1, therefore over-activating NRF2 to alleviate oxidative stress and reduce apoptosis in HCC [ 97 ].…”
Section: Effects Of Trim Proteins On Hallmarks Of Carcinogenesismentioning
confidence: 99%
“…Many studies have reported that the levels of these metabolites are increased in obese people 31 , 32 . Obesity has been found to be a risk factor for HCC 33 , 34 . These metabolites are likely to inhibit the activity of PANK1, thus activating the Wnt/β-catenin signaling pathway and promoting the occurrence and progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, highly reactive molecules react with DNA bases, resulting in pro-mutagenic DNA adducts. Oxidative stress has been shown to contribute to cell migration, invasion, and metastasis in hepatocellular carcinoma [ 43 , 44 , 45 ].…”
Section: Liver and Oxidative Stressmentioning
confidence: 99%